Case report: Light-chain amyloidosis responsive to selinexor in combination with daratumumab and dexamethasone (SDd) therapy - Long, Xiaolu; An, Ning; Li, Chunhui; Zhu, Hui; Li, Haojie; Yu, Qiuxia; Que, Yimei; Xu, Menglei; Li, Zhe; Chen, Wei; Wang, Shuai; Wang, Di; et al. (Frontiers in Medicine, 2024)
The outcome of AL amyloidosis remains poor, particularly in patients with advanced organ involvement which takes long time to recovery. We conducted an observational study of two patients with AL amyloidosis treated with SDd regimen. Both patients successfully achieved significant hematological and organ responses without severe adverse events, and the time to organ response was remarkably shorter than previously reported. Notably, an over 15% reduction in interventricular septal thickness (IVST) was observed in patient#2 within six months. Up to now, SDd therapy has not been previously reported in AL amyloidosis and may be a promising option for these patients.